THE IDENTIFICATION OF PSYCHOLOGICAL WELFARE ON THE SOCIAL AND POLITICAL SCIENCES FACULTY STUDENTS, UNIVERSITY OF LAMPUNG - Aprilia, Hani Damayanti; Caturiani, Susana Indriyati; Rachmawati, Teti; Mahmud, Imam (Srawung: Journal of Social Sciences and Humanities, 2023)
Human beings often suffer a transition period when there is a change in their lives. The change from student to college student has many transitions that sometimes lead to certain crises which differ from each other. Although in Indonesia, there are very few studies that focus on the psychological welfare of students, even though there have been many cases related to the mental health and welfare conditions of students in the campus environment. In general, this research aims to identify the psychological welfare of students in social and political science, University of Lampung. The approach used is mix method approach. The population of this research is active students during the first semester of 2022/2023 based on data obtained from One Data Unila consisting of 4109 students. The research sample was 365 students with an error value of 5%. The research results indicated that generally the respondents’ level of psychological welfare was at a high and very high level. The majority of the 248 respondents had a high level of psychological welfare, and there were no respondents who had a very low level of psychological welfare. The campus environment and the learning process contribute to the dynamics of a student’s life, one of the impacts that may occur is the pressure that can affect the psychological welfare of students and can lead to various psychological disorders in the future. Indeed, a college student cannot avoid the stresses and pressures that occur in college because it is also a form of self-development.